Pengaruh Pendapatan Per Kapita, Tingkat Kemiskinan dan Tingkat Pengangguran terhadap Indeks Pembangunan Manusia pada Kabupaten Tabalong Tahun 2010-2020 - Darman, Rudy; Rahayu, Dewi (PPJP ULM, 2023)
This research discusses the influence of Per capita Income, Poverty Levels, and Unemployment Levels on the Human Development Index (IPM), which will later show whether the contribution of the variable to the dependent variable partially and simultaneously during the period of this research is 2010 to 2020 in Tabalong Regency. The research method used is quantitative descriptive to answer research questions, namely analyzing the influence between variables. Data collection techniques in this study used secondary data, namely documentation from reports and data that already existed at the Central Bureau of Statistics of Tabalong Regency. The data analysis used is the classical assumption test and hypothesis testing using the EViews 9 statistical test application. The results of this study simultaneously are Per capita Income, Poverty Levels, and Unemployment Rates have a positive and significant impact on the Human Development Index of Tabalong Regency in 2010-2020. Partially, only per capita income positively and significantly impacted the Tabalong Regency Human Development Index in 2010-2020. Per capita income is the dominant variable that affects the Tabalong Regency Human Development Index in 2010-2020.